2023
DOI: 10.3389/fphar.2022.1049289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drug-related problems in patients hospitalized in chest disease wards: A randomized controlled trial

Abstract: Objective: According to the World Health Organization (WHO), chest diseases are among the 10 diseases that cause the highest mortality worldwide. Drug-related problems (DRPs), readmission, and antimicrobial resistance are critical problems in chest disease wards. Active involvement of clinical pharmacists (CPs) who are focused on reducing the risks of potential problems is needed. The aim of this study is to investigate the effects of pharmaceutical care (PC) services on the pulmonology service.Method: A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
1
1
Order By: Relevance
“…Studies conducted by internal medicine wards and pharmacy students primarily focused on the proportion of interventions and acceptance rates. The acceptance rate of the recommendations made by the CPR in this study (65%) was lower than reported in the literature (68-96%) [7][8][9][10][14][15][16][19][20][21]. Studies that report high acceptance rates of clinical pharmacy recommendations were conducted in locations where the practice is well-established.…”
Section: Variablescontrasting
confidence: 65%
See 1 more Smart Citation
“…Studies conducted by internal medicine wards and pharmacy students primarily focused on the proportion of interventions and acceptance rates. The acceptance rate of the recommendations made by the CPR in this study (65%) was lower than reported in the literature (68-96%) [7][8][9][10][14][15][16][19][20][21]. Studies that report high acceptance rates of clinical pharmacy recommendations were conducted in locations where the practice is well-established.…”
Section: Variablescontrasting
confidence: 65%
“…The low acceptance rate in this study could be attributed to the hospital's lack of routine clinical pharmacy services and the uncertainty of the healthcare team's attitude towards clinical pharmacists' interventions. Additionally, postgraduate studies in clinical pharmacy in Turkey are typically conducted in the later stages of students' education [9,20,21]. In contrast, this study examines the acceptance rate during the initial residency training phase.…”
Section: Variablesmentioning
confidence: 99%
“…The sample size calculation for the study was conducted based on data from the literature 14 , indicating that DRPs were reduced by an average of 1 per patient in groups where CP made recommendations. The standard deviation was assumed to be 1.…”
Section: Sample Sizementioning
confidence: 99%
“…В другом рандомизированном контролируемом исследовании было показано, что вмешательство клинического фармаколога у больных, госпитализированных в кардиологическое отделение, достоверно снижало количество ПСЛ в сравнении с контрольной группой [49].…”
Section: вмешательство клинического фармакологаunclassified